Violência de gênero contra mulheres na política no estado do Ceará: conceitos, percepções e disputas nas falas de candidatas ao cargo de deputada estadual nas eleições gerais de 2022 - Aragão, Mariana Rodrigues (2024)
This paper seeks to investigate the phenomenon of gender-based violence against women in politics in the state of Ceará, focusing on candidates for the position of state deputy in the 2022 General Elections. The bibliographic research was based on articles, books and academic texts in general that deal with the phenomenon of political gender violence in Brazil and other countries, as well as Law n. 14.192/2021 - currently responsible for bringing the debate on the phenomenon into the law. A documentary analysis was made of the legislation of some Latin American countries, Bolivia, Peru, Panama and Costa Rica, as these countries, like Brazil, have specific legislation on Gender Violence Against Women in Politics. In addition, semi-structured interviews were conducted with 5 women who were candidates in the 2022 General Elections, taking into account different political spectra and social backgrounds. The aim of the research was to find out which laws deal with this phenomenon in Brazil and other Latin American countries and to gather data through interviews to qualitatively analyze how women understand the phenomenon of violence, articulating their statements with existing literature on the subject. To do this, Critical Discourse Analysis (CDA) was used. The work sought to understand how the phenomenon of gender-based violence against women in politics has been understood by women who may be affected by it and how the current norm has helped these women. The main results include (1) the perception of this violence as a naturalized phenomenon; (2) gender as a motivator of this violence; (3) the presence of semiotic violence; (4) the occurrence of violence more in the pre-election and post-election periods than in the campaign period; (5) the perception of the norm as a possible tool in the process of denaturalizing violence; and, finally, (6) the use of the term "Gender Violence Against Women in Politics".